The Strategy Model of Small Industry Development on Woven Business of Pandanus Mat - Syardiansah Syardiansah; Martahadi Martahadi; Suri Amilia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the strategic model for the development of the pandan mat woven industry in Peureulak District, East Aceh Regency. This research is a qualitative research with data collection using informants who are all managers of the pandan mat woven industry in Peureulak sub-district. The instruments used in this study were field notes and interview guides. The results of the data obtained from the informants were analyzed using the interactive model of Miles and Huberman with several stages, namely data collection, data reduction, data display and verifying. In this study, there are two types of data, namely the potential of entrepreneurs in the form of competence and commitment, and business strength / competitive position from internal and external sides. The results showed that to be able to develop the pandan mat woven industry in Peureulak sub-district, a good cooperation between several parties is needed, namely the East Aceh Regency Government, the Peureulak District Government and the Village Head (Geuchik), Raw Material Providers, Distributors (agents) and Village-Owned Enterprises. (BUMG). The East Aceh Regency Government must play a role in fostering the small pandan mat woven industry in terms of policies that support the development of this industry and provide capital assistance so that this industry can continue to survive even in difficult economic conditions. The District and Geuchik governments must play an active role in mentoring and fostering this mat-woven industry to continue to grow by granting legality (business permits) and working capital both in the form of money and equipment for work and always including this industry in every event or exhibition held by the government area. Provision of raw materials to continue to develop the pandan mat woven industry is guaranteed. It is known that this industrial group already has its own land which provides abundant raw material for pandan (seuke). Even if there is a critical shortage of raw materials, it is still easy to get them from a neighboring village that also has pandanus trees. Distributors or agents play an active role in marketing pandan mat woven products and make it easier for people to get pandan mat woven products. Gampong-Owned Enterprises must tie closer together as joint-owned enterprises owned by the village (gampong) as a container for the production of woven pandanus mats so that they can be marketed and make it easier for people to get pandan mats. The Pandan Mat Matting Industry must prepare reliable workforce expertise, guaranteed product quality, use environmentally friendly technology, improve financial administration, increase production and marketing so that it can meet consumer demand.